Indirect Infringement of Intellectual Property in International Documents - Najafi, Hamed (Frontiers in Law, 2024)
It is obvious that mere relying on the domestic laws in intellectual property rights studies and neglecting to pay attention to international documents, is not acceptable, because ultimately, it is international documents that determine and explain the rights and obligations of governments in the international arena. Therefore, it seems necessary to study and review these documents and determine their position regarding the indirect infringement of intellectual property rights and the responsibility arising from it. Several international documents regarding the protection of intellectual property rights have been approved by international assemblies. The Paris Convention for the Protection of Industrial Property Rights, the Berne Convention for the Protection of Literary and Artistic Works (Copyrights), WIPO Internet Treaties and the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), are among the most important documents in this field. This article is dedicated to examine the position of the indirect infringement of intellectual rights in these documents.